Is ethnic and racial identity a potentiating or protective factor in the association between youth victimization and gang-joining? Distinguishing between exploration and affirmation - Mendez, Lucybel (Journal of ethnicity in criminal justice, 2024)
Youth gang membership is a significant public health concern linked to violent victimization. However, not all victimized youth join gangs, highlighting the need to study mitigating factors. Ethnic and racial identity (ERI) is a potential factor, but research has shown mixed results. This study used longitudinal self-report data from the Pathways to Desistance project to examine ERI’s two facets – exploration and affirmation. Findings revealed that victimization increased both ERI aspects, but they had opposite effects on gang-joining. Higher affirmation reduced gang-joining odds and higher exploration increased them. These results highlight the importance of promoting ERI affirmation in gang involvement prevention.